Against cognitive artifacts: Extended cognition theory and the problem of defining artifact. - Vaccari, Andrés Pablo (2017)
Fil: Vaccari, Andrés P. Universidad Nacional de Río Negro. Centro Interdisciplinario de Estudios Sobre Territorios, Economía y Sociedad. Río Negro; Argentina